Doctor Who. Flux, The complete thirteenth series [videorecording (DVD)] - Whittaker, Jodie, 1982-; Gill, Mandip, 1988-; Bishop, John, 1966-; Chibnall, Chris; Chibnall, Chris; Strevens, Matt (BBC, 2022)
She's back. The Thirteenth Doctor is returning for the thirteenth series, a six-part Event Serial. Since their last epic battle in Revolution of the Daleks, the Doctor and Yaz have been exploring the universe together but with the Doctor now questioning everything about her past she will undoubtedly be searching for answers. Series Thirteen will introduce some terrifying new adversaries and the return of truly iconic old enemies. Expect action, fun, scares and extraordinary new worlds as the Doctor and her friends confront a deadly evil.